2014
DOI: 10.1111/jsap.12271
|View full text |Cite
|
Sign up to set email alerts
|

Linear versus non‐linear gastrointestinal foreign bodies in 499 dogs: clinical presentation, management and short‐term outcome

Abstract: RESULTS: A total of 176 dogs had linear and 323 had non-linear foreign bodies. Dogs with a linear foreign body were more likely to have a history of vomiting, anorexia, lethargy and pain on abdominal palpation. They were also more likely to have the foreign body anchored in the stomach and continuing into the small intestine, experience intestinal necrosis, perforation and peritonitis, and require intestinal resection and anastamosis. The duration of hospitalisation was longer for dogs with linear foreign body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
51
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 14 publications
14
51
5
2
Order By: Relevance
“…The most common indications for gastrointestinal surgery include gastrointestinal foreign bodies, neoplasia, gastric dilatation‐volvulus, and surgical biopsies . Many surgical techniques have been described for closure of gastrointestinal incisions, including different suture materials and patterns, anastomotic rings, skin staplers, and linear stapling devices .…”
Section: Introductionmentioning
confidence: 99%
“…The most common indications for gastrointestinal surgery include gastrointestinal foreign bodies, neoplasia, gastric dilatation‐volvulus, and surgical biopsies . Many surgical techniques have been described for closure of gastrointestinal incisions, including different suture materials and patterns, anastomotic rings, skin staplers, and linear stapling devices .…”
Section: Introductionmentioning
confidence: 99%
“…However, gastrointestinal surgery carries risks that do not occur with endoscopy, such as generalised peritonitis associated with wound dehiscence or the spillage of gastric contents intra-operatively (Bebchuk 2002). Furthermore, following surgery for discrete GFBs, dogs were hospitalised for a median duration of 2 days compared to 1 day in the cats that underwent endoscopy in the present study (Hobday et al 2014). Surgical risks are increased with OFB.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, following surgery for discrete GFBs, dogs were hospitalised for a median duration of 2 days compared to 1 day in the cats that underwent endoscopy in the present study (Hobday et al . ). Surgical risks are increased with OFB.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,5 Successful endoscopic retrieval of gastric foreign bodies has been reported in 63.5-90% of cases. 6,7 Gianella et al reported a 12.7% complication rate, including perforation (gastric or esophageal), esophageal stricture, esophageal diverticula, peri-esophageal abscess, pneumothorax, pleural effusion, and respiratory arrest. 6 Six percent of patients died or were euthanized in that study.…”
Section: Discussionmentioning
confidence: 99%